Legal Protection of Uncertified Waqf Land in Indonesia - Mutiara Hamdalah Munandar (Nurani Hukum, 2021)
This study aims to determine the legal protection of uncertified waqf land in Indonesia. This research uses descriptive analysis, which describes the fact or certain legal events that occur in society. The result of this research is that waqf land that does not have a certificate can be protected by law. It is a waqf land that meets the terms and conditions and can be proven, judges of the Religious Court are of the opinion that the waqf land without a certificate can be guaranteed its protection with the Wakaf Pledge Deed and witnesses and evidence. other written documents that clearly explain the position of the donated land. The public is of the opinion that a waqf will be guaranteed protection when it has been used for religious purposes or other public interests. In the future, it is hoped that all parties will have a correct understanding of the procedures and processes of waqf, that waqf is not only up to having AIW  but waqf land must be registered with the National Land Agency and have a certificate to guarantee its legal protection.Keywords: Waqf; Certificate; Religious Court.